Comparative analysis of AC and DC bus configurations for flywheel-battery HESS integration in residential micro-grids. (1st August 2020) - Barelli, L.; Bidini, G.; Pelosi, D.; Ciupageanu, D.A.; Cardelli, E.; Castellini, S.; Lăzăroiu, G.
Abstract: With the rapid increase in renewable energy sources (RES) and distributed generation (DG), the integration of hybrid storage energy systems (H-ESS) have a key role to ensure networks safe operation. Furthermore, they can enhance power systems stability while supplying the local loads, supporting RES integration and sustainable energy systems development. In this paper, a specific residential Micro-Grid (MG), composed by a photovoltaic plant coupled with a battery-flywheel H-ESS is presented. As an innovative contribution with respect to the literature, the study provides a quantitative comparison between dynamic performances of two possible MG electrical architectures (AC bus and DC bus) under different operating conditions. It results that, the AC architecture enables improved current evolution at the grid interface (peak current value is reduced by 58% and transient time is 30% shorter). Since different power electronic devices are implemented in the AC and DC bus architectures, the Total Harmonic Distortion is assessed to quantify their impact on current and voltage waves. These results indicate that the AC bus MG is the better option for the considered configuration. Moreover, AC bus MGs could be an excellent solution for developing DG networks, especially considering its integration and compatibility features with pre-existing power grids infrastructures. Highlights: AC and DC bus MG configurations are compared for integrating HESS coupled to RES. Simulations are performed in representative conditions and MG dynamics is examined. AC architecture proves to reestablish the balance towards the grid faster by 30%. At the point grid monitoring point, the peak current is halved in the AC architecture. AC bus configuration is compatible with pre-existing power grids infrastructures.